Fruit peel waste as a novel low-cost bio adsorbent - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Reviews in Chemical Engineering, 2015)
Fruit peel waste (FPW) is abundantly available from the agricultural and food processing industry and has been studied in recent past as an adsorbent. This paper critically reviews the reported work and investigates various FPW-pollutant systems. The study includes statistics of FPW generation, modification, characterization, adsorption ability, recovery/regeneration, and modeling (isotherms, kinetics, and thermodynamics) of batch adsorption. It is found that orange and banana peels are the most extensively studied adsorbents, whereas Pb2+ and methylene blue are the most efficiently removed pollutants, the Langmuir and Freundlich adsorption isotherms provide the best fit in most of the cases, and in general, pseudo-second-order kinetics is followed. There are very limited column studies and no report on commercial plant. Though the reproducibility of the results is poor, FPW has a great potential in the wastewater treatment due to its abundant and cheap availability. FPW can be used for removal of heavy metals and dyes; however, removal of organic and gaseous impurities needs further investigation.
Keywords: adsorbent; Adsorption; fruit peel waste; organic and inorganic pollutants; wastewater

Fruit peel waste: characterization and its potential uses - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2017)
Globally, India is the leading producer of fruits. Fruits after consumption leave a peel which is a nuisance to the environment as a solid waste. In this article, commonly available large volume-fruit peels (FP) (viz. banana, orange, citrus, lemon and jackfruit) were investigated for surface, physical and chemical characteristics with a view to propose their valorization in detail. Each FP was characterized by proximate and ultimate analysis, porosity, particle density, bulk density, point of zero charge (pH(pzc)), surface pH, surface charges, water absorption capacity, BET surface area, scanning electron microscopy, Fourier transform infrared spectroscopy and TGA/derivative of thermogravimetric. The BET surface area of FP is very less, between 0.60 and 1.2 m(2)/g. The pH(pzc) and surface pH values of orange peel (OP), citrus peel (CP), lemon peel (LP) and jackfruit peels (JFP) are in the range of 3-4. The pH(pzc) value and surface pH of banana peel (BP) is closer to 7. The order of surface acidity is OP > LP > CP > JFP > BP. From TG curves it is clear that FPs are stable below 150 degrees C. The results will be useful for rational design, when FP is used as a substrate for bioactive compounds, phenolic antioxidants, organic acids, enzymes, biofertilizer, production of energy and as adsorbents.